2010
DOI: 10.1152/ajprenal.00683.2009
|View full text |Cite
|
Sign up to set email alerts
|

Progressive histone alterations and proinflammatory gene activation: consequences of heme protein/iron-mediated proximal tubule injury

Abstract: Zager RA, Johnson AC. Progressive histone alterations and proinflammatory gene activation: consequences of heme protein/iron-mediated proximal tubule injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Nath et al [16] described that repetitive episodes of rhabdomyolysis induced an attenuated renal response to weekly glycerol IM injections after one month, also resulting in a mild decrease in CrCl (≈-15%) and absent structural kidney changes were reported at this time point. Nevertheless, rhabdomyolysis induced a persistent and increasingly pro-inflammatory state in the kidney, despite the apparent AKI resolution [20]. In the present study, we combined both insults to resemble heat stress nephropathy and found a 45% fall in CrCl, a further increase in NAG urine excretion (in comparison to W + V group reported in ref.…”
Section: Discussionsupporting
confidence: 55%
“…Nath et al [16] described that repetitive episodes of rhabdomyolysis induced an attenuated renal response to weekly glycerol IM injections after one month, also resulting in a mild decrease in CrCl (≈-15%) and absent structural kidney changes were reported at this time point. Nevertheless, rhabdomyolysis induced a persistent and increasingly pro-inflammatory state in the kidney, despite the apparent AKI resolution [20]. In the present study, we combined both insults to resemble heat stress nephropathy and found a 45% fall in CrCl, a further increase in NAG urine excretion (in comparison to W + V group reported in ref.…”
Section: Discussionsupporting
confidence: 55%
“…Evidence shows that TGF-␤1 can regulate epigenetic modifications to regulate target genes in diverse cell types, including vascular smooth muscle cells (42), ovarian (63), and mammary epithelial cells (61), immune cells (66), and fibroblasts (15). Reports show that histone modifications including H3K9Ac and H3K4 methylation (H3K4me) play a role in PMA-induced laminin gene expression in rat mesangial cells (35) and in inflammatory gene expression in tubular cells from acute renal injury models (34,65). Our recent studies demonstrated that TGF-␤1 can induce significant changes in promoter histone H3K4me and H3K9me at the promoters of differentially regulated profibrotic genes CTGF, Col1a1, and PAI-1 in MCs (51).…”
Section: F607 Histone Acetylation In Tgf-␤1-mediated Actionsmentioning
confidence: 99%
“…Complex interactions between heme oxygenase and TGF-β1, over time, in specific cell subsets, may have ameliorative or maladaptive consequences. 15,58,59 The lack of renal tissue from patients with AKI and suitable controls has been identified as a barrier to enhancing our understanding of factors associated with outcomes in patients with AKI. 2,60 The National Institute of Diabetes, Digestive and Kidney Diseases (NIDDK) supports the Assessment, Serial Evaluation and Subsequent Sequelae of AKI (ASSESS AKI) study, which prospectively evaluates long-term outcomes of hospitalized patients, with and without CKD, after an episode of AKI, to determine the natural history of AKI and delineate risk factors for progression and development of complications, including CVD.…”
Section: Mechanisms Associated With Progressive Renal Injurymentioning
confidence: 99%